Increasing the Capacity of Padang City Community Against Covid-19 Disaster Management - Roni Ekha Putera; Tengku Rika Valentina; Putri Febri Wialdi; Nia Audia (Jurnal Public Policy, 2022)
The purpose of this study is to describe how efforts are being made to increase public understanding of non-natural disaster management, in this case the COVID-19 pandemic. This study uses a descriptive approach, with methodological techniques using interviews, documentation and literature studies. In dealing with COVID-19, of course, it is not only the duty of the government, but also the role of the community in the process of dealing with this pandemic disaster. In this regard, the community's understanding and ability to recognize the COVID-19 response system is needed. Therefore, based on the research conducted, the results show that in terms of quantity the capacity has been fulfilled, but when viewed in terms of quality there are still limitations. So the conclusion is there needs to be an increase in the rate of human resources by providing direct and periodic training and education. By continuing to carry out the Covid health protocol